Impact of microplastics on the in situ, high-resolution of key nutrient dynamics at the soil-water interface in rice fields - Jiang, Yizhen; Zhu, Xiaoyan; Zhang, Siyuan; Yang, Jingang; Lu, Yongzheng; Wang, Ying (Frontiers in Environmental Science, 2023)
Appreciate for giving us the opportunity to improve our manuscript.Your comments and those of the reviewers are highly insightful and enable us to greatly strengthen the quality of our manuscript. We have revised the manuscript based on your kind and constructive suggestions. The following pages are our point-by-point responses to each of the comments from the reviewers. If there are more questions, we are willing to revise it again.We sincerely wish this manuscript will be finally published on Frontiers in Environmental Science.Thank you very much for all your help, and we look forward to hearing from you soon.Responses to editor and reviewers 1. The description about the experimental design was not clear. The pot was 25 cm in diameter and 20 cm height, and 8 kg of soil was added? Dry soil or wet soil? the water content? Any overlying water?Response: We appreciate this valuable comment. With careful check, these pots have dimensions of 25 cm in length, 20 cm in width, and 28 cm in height, and 8 kg of dry soil was added for each pot. Please refer to the photos below. The rice plants were watered following standard management practices, usually with ~5cm overlying water.Response: Thanks for this great comment. The depth for treatment LL is different from the others due to that the film was broken during cutting by accident. We added the following note in the revised manuscript. "Note: The depth for treatment LL was shorter 25mm due to accidently broken." Please see lines in 178-179.